Epistemologies of Inclusion across Continents and Cultures: Radical Realism and Storytelling - Carr, Anne (2025)
For any story, what matters is how it is told and heard. Rutherford describes storytelling as action-guiding. It can allow a division of labor between the teller(s) and the reader(s)/ listener(s). Simply by the story being told, normatively justified forms of action can be inferred. Although this account of storytelling looks more prescriptive than realist, noone is compelled upon reading or listening to it to follow it regardless of how exacting it is. Stories, provided we are epistemically just in our reading and listening, can overcome the dichotomy between prescriptive and interpretive understandings. The opening up of this possibility can furnish contemporary realists with non-moralist and non-status quo affirming normative precepts. Starting from the recognition that how we know reality and how we articulate that knowledge scaffolds how our research processes, we can reconfigure and invent revised judgments about the limits of (political) educational possibility. Through evidence based on collaborative practice, interdisciplinary groups of undergraduate higher education students from the global south and north, virtually navigated the multiple perspectives of volatility, unpredictability, and complexity of our interrelated world through migration stories. By expanding their collective capacity to hold space for difficult conversations about the stories they heard, they opened up the possibility of furnishing non-moralist and non-status quo affirming normative precepts.